INTEGRATIVE AND INTERCONNECTIVE PARADIGMS IN ISLAMIC EDUCATION - Munis, Ibnu Da’i; Pranoto, Ahmad Hadi; Nurhuda, Abid; Ahmad, Walid In’am; Putri, Yulita (CV. Mitkom Indotama, 2026)
The integrative-interconnective paradigm in Islamic education emerges as a response to the dichotomy between religious and scientific knowledge. This paper aims to explore the philosophical foundations, epistemological structure, and practical implications of this paradigm in the development of Islamic education in Indonesia. Using a library research method, this study analyzes various scientific sources, including works by Amin Abdullah, Al-Faruqi, and Al-Attas. Findings show that the integrative-interconnective paradigm encourages the unity of knowledge based on wahdat al-'ilm, which bridges bayani, burhani, and 'irfani epistemologies. This paradigm has been applied in several Islamic higher education institutions, such as UIN Sunan Kalijaga and UIN Jakarta, through curriculum reform, research integration, and the development of interdisciplinary centers. This study concludes that the paradigm offers an epistemological and practical framework that strengthens Islamic education toward holistic and transformative learning.